Antimicrobial effects of moringa oleifera seeds on E. coli K-12 derivatives - Zhou, Lingyan (2018)
Water treatment in developing areas is still not up to standards, while people are highly vulnerable to polluted water. In Nepal, the water body has been found to be pervasively contaminated with Escherichia coli (E. coli). Such water has been used for washing produce and irrigation on a daily basis, posing various health hazards to the people and the surrounding environment. However, conventional disinfection treatments such as chlorine, ultraviolet radiation, and ozone treatment, as well as traditional flocculant chemicals, are cost-prohibitive for rural communities. Hence, sustainable alternatives to disinfect water using locally available resources are preferable. Moringa oleifera (MO) seeds can be found in abundance within the same region and many other tropical as well as subtropical places. These seeds have been suggested to have the potential of inactivating E. coli, yet previous studies so far focused mostly on its properties for coagulation and turbidity reduction. Evidence provided in the literature is sparse, and a review summarizing the current state of this alternative treatment is lacking. This paper has two aims: First, to provide a literature review summarizing the current state of knowledge in the use of MO seeds as a turbidity reduction and disinfecting agent; second, to explore the inactivation of E. coli in water through MO seeds treatment. The review of previous studies done by researchers around the world has substantiated the coagulating and antimicrobial properties of MO seeds as well as its wide range of applicability geographically, by identifying several functional proteins, acids or lectins in the seed extract. However, there is up to date yet a consensus on the active components that are the most crucial for the water treatment capabilities of MO seeds, as well as on the optimal seed dosage and conditions. The synthetic contaminated water samples for experiments in the project were prepared with E. coli strain K-12 MG1655, and the experiments were conducted mainly through jar test and drop plate techniques. The experimental results showed a proportional relationship between the reduction in E. coli and turbidity levels of the water sample, of which higher initial turbidities (and E. coli concentrations) gave rise to better E. coli inactivation by MO seeds treatment. The optimal dosage concentrations were also found to be different for samples with varied initial E. coli concentrations. MO seeds, owing to their coagulating and antimicrobial properties, undeniably have huge potentials and benefits at relatively low cost for water treatment, despite current knowledge limitations and practical application challenges. With continuous research and development, the great underlying values of MO seeds in this regard could be harnessed in the near future.